Pengembangan Program Pedidikan Karakter Melalui Pendekatan Sistem - Dwi Asri; Tiara Lubis; Anysah Daulay; Abdul Fattah Nasution (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Especially in the face of the challenges of globalization and complex social changes, character education is very important to develop quality human resources. Library research methods and case studies are used in this study to achieve the goal of creating a system-based character education program. Literature reviews discuss the literature on the theory and practice of character education, while case studies show how these methods are used in certain situations. Character education programs use a systems approach, which combines various aspects, such as curriculum, learning techniques, school environment, family, and community involvement, to produce a sustainable and mutually supportive educational process. The results of this study show that the systems approach allows for a more effective character education program compared to the partial or limited approach to the school environment only.